Relationship between hyperlipidemia and the gut microbiome of rats, characterized using high-throughput sequencing - Yaqi Li; Quantao Ma; Jingkang Wang; Pengfei Li; Long Cheng; Yongcheng An; Yuhui Duan; Hongyu Dai; Ting Wang; Baosheng Zhao (Journal of Traditional Chinese Medical Sciences, 2020)
Objective: To determine the effects of a high-fat diet (HFD) on the gut microbiome in rats, to explore the relationship between the intestinal flora and blood lipid profile. Methods: Sprague–Dawley rats were fed an HFD for four weeks to induce hyperlipidemia, then 16S rRNA sequencing was used to compare the intestinal flora between hyperlipidemic and control diet-fed rats. Results: The microbiome of rats fed an HFD for four weeks differed from that of control diet-fed rats. Bacterial species that were less abundant were most affected by HFD feeding, among which were many pathogenic species, which became significantly more abundant. Eighteen genera were present in significantly different numbers in hyperlipidemic and control rats, more than half of which have been linked to infection and inflammation, or energy intake and obesity. The results indicated a type of stress response of the flora to a high-fat environment. In addition, the age of the rats tended to influence the gut microbial composition. Conclusion: These findings suggest that HFD may induce hyperlipidemia by affecting the gut microbial composition. Changes in the abundance of pro-inflammatory and pathogenic bacteria, and those that influence energy intake and obesity, may be important mediators of this.